Co‐microencapsulation of ammonium polyphosphate and aluminum hydroxide in halogen‐free and intumescent flame retarding polypropylene. Issue 4 (24th October 2013) - Zheng, Zaihang; Sun, Huimin; Li, Wenjie; Zhong, Shuangling; Yan, Juntao; Cui, Xuejun; Wang, Hongyan
<x xml:space="preserve">Abstract</x> In this article, co‐microencapsulated ammonium polyphosphate (APP) and aluminum hydroxide (ATH) [M(A&A)] was prepared by using 4, 4'‐diphenylmethane diisocyanate (MDI) and melamine (MEL) via in situ surface polymerization method. The chemical composition of M(A&A) was confirmed by Fourier transform‐infrared spectra (FT‐IR). Thermal behavior and surface morphology of M(A&A) were systematically analyzed by thermogravimetric analysis (TGA) and scanning electron microscope (SEM), respectively. Water solubility tests indicate that water solubility of M(A&A) decreases greatly than un‐microencapsulated ones. Besides, flame retardant properties of polypropylene (PP) compositing with M(A&A) were investigated by limiting oxygen index (LOI), vertical burning tests (UL‐94) and cone calorimeter. The results demonstrate the LOI value of PP composites is improved after combining with co‐microencapsulated flame retardants. Compared with PP/A&A, the peak heat release rate of PP/M(A&A) decreases from 210 to 120 kW/m2 at the same flame retardant loading level. Moreover, in order to investigate the flame retardant mechanism, the char residue of PP composites after combustion was studied by optical photos, X‐ray photoelectron spectroscopy (XPS) spectra and FT‐IR. POLYM. COMPOS., 35:715–729, 2014. © 2013 Society of Plastics Engineers